Probenecid as a Noninjurious Positive Inotrope in an Ischemic Heart Disease Murine Model. (May 2013) - Koch, Sheryl E.; Tranter, Michael; Robbins, Nathan; Luther, Kristin; Singh, Umesh; Jiang, Min; Ren, Xiaoping; Tee, Trisha; Smith, Leah; Varma, Priyanka; Jones, W. Keith; Rubinstein, Jack
The current therapeutic options for acute decompensated heart failure are limited to afterload reducers and positive inotropes. The latter increases myocardial contractility through changes in myocyte calcium (Ca 2+ ) handling (mostly through stimulation of the β-adrenergic pathways [β-ADR]) and is associated with paradoxical effects of arrhythmias, cell death, and subsequently increased mortality. We have previously demonstrated that probenecid can increase cytosolic Ca 2+ levels in the cardiomyocyte resulting in an improved inotropic response in vitro and in vivo without activating the β-ADR system. We hypothesize that, in contrast to other commonly used inotropes, probenecid functions through a system separate from that of β-ADR and hence will increase contractility and improve function without damaging the heart. Furthermore, our goal was to evaluate the effect of probenecid on cell death in vitro and its use in vivo as a positive inotrope in a mouse model of ischemic cardiomyopathy. Herein, we demonstrate that probenecid induced an influx of Ca 2+ similar to isoproterenol, but does not induce cell death in vitro. Through a series of in vivo experiments we also demonstrate that probenecid can be used at various time points and with various methods of administration in vivo in mice with myocardial ischemia, resulting in improved contractility and no significant difference in infarct size. In conclusion, we provide novel data that probenecid, through its activity on cellular Ca 2+ levels, induces an inotropic effect without causing or exacerbating injury. This discovery may be translatable if this mechanism is preserved in man.